Analysis Of Factors Influencing Tax Management In Manufacturing Companies On The Idx In The 2021-2023 Period - Margareta Febe; Bella Novianti (International Journal of Multidisciplinary Sciences and Arts, 2025)
The decline in company profitability is a problem that needs to be of concern to many parties. Declining profitability will affect the taxes received. The weakening trend in tax revenue from the manufacturing side should be watched out for considering that this sector is relied on to contribute to state revenue and support economic growth. The research data used in this study is secondary data obtained from audited financial reports and annual reports of companies in the Idx-Ic Manufacturing Sector for the 2021-2023 period. The research and testing methods used were the Purposive sampling method, Classical assumption testing, Multiple regression analysis test and Partial t test. The results of this model that no single variable x has a significant influence. The results of this study provide different results compared to previous studies which showed that there was a significant influence, both positive and negative. Further research suggestions use the director or board of directors variable because the director is responsible for the company's operations.